Children's theater performance "Buta Grana Ireng" reinterpretation of Sudamala story in Demping Village - Bagong Pujiono; Handriyotopo Handriyotopo; Catur Nugroho; Tatik Harpawati; Delfin Febriansyah; Dela Cahyaning Permata; Arieska Wulandari (Gelar : Jurnal Seni Budaya, 2023)
Demping, as a tourist village located in Karanganyar Regency, Central Java, has a variety of exciting tourism potential, both natural and religious. The lives of people who are predominantly Hindu still adhere to customs and various activities of religious traditions that are in synergy with their natural beauty. One thing that attracts attention is the public's trust in Sudamala's story. Sudamala tells the story of Durga, ugly and evil until she becomes the beautiful and kind Goddess Uma. Starting from this story, this research attempts to develop it into a children's theater performance by highlighting the values of the Sudamala story. The approach used is a deconstruction perspective from "sanggit" reinterpretation, namely, re-understanding the meanings contained in the story of the Sudamala text with a new meaning. Through this analysis, we can understand in depth the contents of Sudamala's literary works, which are then worked out skillfully in the theatrical work of Buta Grana Ireng children. In the end, the reinterpretation of sanggit in the theatrical performance of the Buta Grana Ireng children was generally able to increase the appreciation of the new theatrical work from the reinterpretation of the Sudamala story at the Sukuh temple and became a new performance work in the Demping Tourism Village.